(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
In this paper, we study the concept of q-fuzzy n-lie sub algebras (ideals) of lie algebras and investigate some of their properties. We discuss the relationship between q-fuzzy lie sub algebra (respectively ideals) and Lie sub algebras (respectively ideals). For a finite number of q-fuzzy n-lie sub algebras, we construct new q-fuzzy n-lie sub algebras on their direct sum. Finally, we analyze the homomorphism concept of q-fuzzy n-lie sub algebra over ideals.